Implementation Of Mobile Web Applications Using Balanced Scorecard KPI Formulation - Suharto, Agus; Zein, Afrizal (Journal of Information System, Technology and Engineering, 2024)
Implementation of mobile web applications has become a key factor in improving organizational performance in the digital era. This research examines the application of the Balanced Scorecard (BSC) model in the formulation of Key Performance Indicators (KPI) for mobile web applications to increase operational effectiveness and efficiency. The Balanced Scorecard, developed by Kaplan and Norton, is a managerial tool that integrates multiple performance perspectives financial, customer, internal processes, and learning and growth in one comprehensive framework. This study focuses on how KPIs designed based on the BSC model can be used to assess and monitor the performance of mobile web applications. The implementation process begins with identifying the organization's strategic objectives and establishing relevant KPIs for each BSC perspective. Next, this research evaluates how these KPIs are applied in the context of mobile web applications and their impact on application performance and user satisfaction. The results of this research show that the use of BSC-based KPIs can increase visibility of mobile web application performance, assist in identifying areas of improvement, and support better strategic decision making. This research also identifies challenges that may be faced in implementing the BSC model in the context of mobile technology and provides recommendations to overcome these challenges.